PENGARUH DAYA TARIK IKLAN TERHADAP NIAT PEMBELIAN ULANG SKINTIFIC DI TIKTOK DIMODERASI CELEBRITY ENDOSER - Ramdhania, Novi; Erniawati, Erniawati; Khasanah, Aprilia Pramudita; Rahmawati, Anik; Rahadhini, Marjam Desma (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This study aims to determine the relationship between advertising attractiveness on Skintific’s repurchase intention on the Tiktok platform which is moderated by celebrity endosers. This research is a quantitative study with primary data sources obtained from distributing questionnaires via google form. Data for this study were obtained from 71 respondents who are Slamet Riyadi University students who have seen Skintific advertisements on Tiktok, know Skintific celebrity endosers, and have purcashed Skintific products on Tiktok. The data analysis method uses MRA (Moderating Regression Analysis) with the help of SPSS version 22. The results of this study indicate that the advertising attractiveness variable has a positive effect on repurchase intention, the celebrity endoser variable has a positive effect on repurchase intention, and the celebrity endoser is proven to weaken the relationship between advertising attractiveness and Skintific repurchase intention on the Tiktok platform.